Transpiration intensity in submediterranean species Trifolium patens from three meadow associations of mountain Radocelo (Serbia) - Dajic Z.; Kojic M.; Vrbnicanin S.; Mrfat-Vukelic S. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
The submediterranean species Trifolium patens Schreb. is known as a very good quality forage crop, spread in various types of valley and hilly meadows in Serbia. As transpiration intensity may indicate different ways of water balance mechanisms in plants, the diurnal changes of transpiration have been determined in this species grown in three meadow associations at Rudnjanska upland and mountain Radocelo: ass. Danthonietum calycinae, Agrostietum vulgarae and Koelerietum montanae. Transpiration curves in Trifolium patens have indicated the moderately stabile water regime of this species, where water restriction was partly endogenously regulated during the hottest period of day in ass. Danthonietum calycinae. The highest values of transpiration intensity have been recorded in ass. Koelerietum montanae, which mostly develops on shallow, poor and dry soil. Generally, transpiration intensity was clearly dependent on environment, i.e. microclimatic factors.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)